2008
DOI: 10.1007/s11707-008-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the change of major lakes on the Qinghai-Tibet Plateau in the last 25 years

Abstract: On

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 2 publications
2
26
0
1
Order By: Relevance
“…It receives inflow from a river to the west and flows northeastwards to the Yellow River. Figure 4c [4,6,7]. Since June 2004, the local government imposed a measure to protect the grassland in this region [41].…”
Section: (I) Lakes With Varying Lake Level Trendsmentioning
confidence: 99%
“…It receives inflow from a river to the west and flows northeastwards to the Yellow River. Figure 4c [4,6,7]. Since June 2004, the local government imposed a measure to protect the grassland in this region [41].…”
Section: (I) Lakes With Varying Lake Level Trendsmentioning
confidence: 99%
“…Bangong Co is mainly recharged by runoff, and the decreased precipitation and increased temperature have led to a decrease in lake area (Shao et al, 2007).…”
Section: Analysis Of the Reasons For Lake Changesmentioning
confidence: 99%
“…It has been concluded that the major mechanism for drying water bodies in no-permafrost zone was decreased water balance in a warming climate (Klein et al 2005). The shrunk and split of Gyaring Hu, Ngoring Hu, Xinxinhai, Xinsuhai, Duogcuorengiang, Mitijiangmuco, Rumchanco and Wupuemoco Lake in the Tibetan Plateau could be applied to validate the mechanism (Guo et al 2003;Bian et al 2006;Shao et al 2007;Li et al 2008;Wu et al 2008;Niu et al 2008). There also observed a spatially patchy process related to permafrost distribution rather than a direct climatic mechanism such as increased evaporation.…”
Section: Introductionmentioning
confidence: 99%